PKM Bagi Madrasah Ibtidaiyah Muhammadiyah Di Kecamatan Salam Kabupaten Magelang - Ahwy Oktradiksa; Kanthi Pamungkas Sari; Irham Nugroho (Publikasi Pendidikan, 2018)
MIM Jagalan (1950) and MIM Jumoyo (1968) is a Basic Education Institution in Salam Sub-district, Magelang. Although it has been half a century established, but until now still experiencing a number of obstacles, among which are 1) the low knowledge and understanding of the National Education Standards (SNP) so that the impact on the implementation of quality education process; 2) the existence of gaps in the implementation of primary education (MI and SD) in Salam District Magelang regency; 3) The objective conditions of teachers and human resources and the resources of instructional media for educational visual aids (APE) so as to impact on the limitations in supporting quality learning process; 4) The lack of support of madrasah stakeholders in the development of madrasah both morally and materially. In relation to this matter, it is a community service activity that aims to improve the quality of madrasah to madrasah with quality education process. The method to be used in the achievement of the objective is Participatory Rural Appraisal (PRA) participatory community empowerment model. The method is divided into three stages: preparation, implementation and mentoring, and preparation of reports. The preparation phase begins with permission, preparation through Forum Group Discussion (FGD) division of implementing tasks with partners. Implementation phase begins with socialization, SNP evaluation, document quality assurance, APE development assistance, strategy training and learning method, final stage of preparation of final report.